The measurement of close hydrostatik circuit by LabView - Kriššák, Peter; Strážovec, Igor; Božek, Jozef (Communications - Scientific letters of the University of Zilina, 1999)
In most cases, the personal computer (PC) can emulate traditional measurement and automation control instruments in industry, no matter which departments use it. The PC’s extensive capabilities enable to create personalized, flexible systems with more possible implementations than traditional tools. Once a system is created, it is easy to change it for different applications without buying new equipment. In this paper, a computer based measurement system of close hydrostatic circuit and its static and dynamic characteristics acquired by application of LabView graphical programming software is presented.